ACQUIRED HEMOPHILIA IN PATIENTS ON ORAL ANTICOAGULANT THERAPY – CASE REPORT - Ljubičić, Jelena (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: Acquired hemophilia is a severe, sometimes even fatal condition of impaired coagulation. It most often leads to severe mucocutaneous, gastrointestinal, urinary, and, rarely, intracranial bleeding. This disorder occurs due to the production of antibodies against clotting factor VIII (F VIII), which interfere with its normal function. In laboratory analyses, prolonged activated partial thromboplastin time (aPTT), which cannot be normalized after being mixed with pooled normal plasma, is noticeable. Case report: In this article, the clinical course of the disease is described in a patient with acquired hemophilia, who was treated with oral anticoagulant therapy, and who initially also had prolonged prothrombin time, measured in international normalized ratio (INR) units, which measure how long it takes for a clot to form in a blood sample. Hemorrhagic syndrome was explained by iatrogenic effect. However, since bleeding continued after INR normalization, it was suspected that there was a different cause of hemorrhagic syndrome. The aPTT mixing test was performed (mixing an equal volume of the patient’s plasma and normal pooled plasma (NPP) and repeating the aPTT test immediately and after one-hour incubation), after which the aPTT remained prolonged. This proved the presence of coagulation inhibitors, which is why acquired hemophilia was suspected. The patient was referred to a tertiary medical institution for further diagnostics and treatment. Conclusion: The objective of this case report is to show that patients with hemorrhagic syndrome, who are on anticoagulant therapy, may develop hemorrhagic syndrome for a different, non-iatrogenic reason. The purpose of the study is to draw the attention of medical doctors to various causes of hemorrhagic syndrome in patients receiving anticoagulant therapy.